Characterization of material constraint effects on creep crack growth for welded joints by a new constraint parameter QM*. (December 2021) - Jing, Hongyang; Xiong, Yu; Zhao, Lei; Xu, Lianyong; Han, Yongdian
Highlights: Effect of creep mismatch on the creep crack growth behavior was studied in different mismatched conditions. A new load-independent material constraint parameter Q M * was introduced. Variation of CCG behavior under different mismatch levels was well characterized by Q M * . Abstract: The effect of creep mismatch on the creep crack growth was studied with a wide range creep mismatch factors and mismatch widths. Moreover, the influences of cracked specimen geometry were considered. The creep crack growth was accelerated in an undermatch and slowed in an overmatch, influenced by the weld width and the specimen geometry. Furthermore, a new load-independent constraint parameter Q M * was introduced to quantify the material constraint induced by material mismatch. Q M * was employed to correlate with the normalized creep crack growth rate. This method could well demonstrate the variation of creep crack growth rate under different mismatched conditions.